Legal regime on food contracts in Spain: Freedom of agreements and mandatory contractual conditions - Amat Llombart, Pablo (Przegląd Prawa Rolnego, 2022)
This article examines the main measures adopted by Spanish law 12/2013 on improving the functioning of the food chain, recently amended. The starting point of the deliberations was the correct determination of the type of commercial and legal relations between chain operators, to which the discussed legislation applies. Next, the legal regime on the food contract which is mandatory for most transactions between suppliers and buyers of agricultural and food products was analysed. This involved the examination of the concept, the nature and types of food contracts. The Spanish legislation is halfway between the recognition of the freedom of agreements concluded by parties and the imposition of certain mandatory requirements on parties entering into contracts. Food operators must be aware of the formal requirements imposed on them in private contracts (regarding both their content an form), the main aspects of which have been analysed in the article.